(untitled) (Al-Academy, 2019)
Scenes of love constitute a large space within the orbit of the movies, so that there is almost no film (no matter what kind) void of these scenes, as they are associated with many dimensions and they constitute a major attraction for viewers, and thus the direction solutions and their connection to the director’s vision constitute a large part in the process of employing signs to highlight what should be highlighted or to refer to it symbolically on the grounds that the director does not have full freedom in the transfer of scenes of love at all levels as they are in reality. The research included three sections within the theoretical framework:The first section: the concept of image and its rhetorical importance. This section discussed the importance of the image as a cultural entity and the frequent circulation in the modern era because of what it possesses of a large amount of intended information.The second section: the symbolic work of the cinematic image, which talks about the concept of the mark, and how it works in the cinematic image.The third section: the production of significance in the structure of the scene. This section talks about how to use the mark through channels of communication to produce significance